A STUDY ON JOSE MOURINHO’S LEADERSHIP SKILLS AND PERFORMANCE ON FOOTBALL CLUBS - Heng, Shao Jie; Syriac, Nellikunnel (INTI International University, 2023)
This study delves into the distinctive leadership style of Jose Mourinho, a highly acclaimed football manager known for his strategic acumen, charisma, and a track record of success with top-tier clubs. Mourinho's leadership philosophy is characterized by a unique blend of tactical brilliance, motivational prowess, and an ability to foster a winning mentality within his teams. The paper explores Mourinho's early career, tracing his rise from an assistant coach to his breakthrough with FC Porto and subsequent managerial roles at renowned clubs such as Chelsea, Inter Milan, Real Madrid, and Manchester United. It analyzes the key elements of Mourinho's leadership, emphasizing his tactical innovations, man-management skills, and the capacity to instill a winning culture in diverse football environments. Mourinho's tactical approach is dissected, highlighting his adaptability and strategic flexibility, evident in successful campaigns across different leagues. His charisma and ability to command respect from players are examined, offering insights into how Mourinho builds strong team dynamics and maximizes player performance. Furthermore, the paper explores the challenges Mourinho has faced during his managerial career, including controversies and high expectations. It discusses how his leadership style has evolved in response to changing football landscapes and the demands of different clubs. Drawing from his management and team performance. this research aims to provide a comprehensive understanding of his leadership philosophy. The study contributes to the broader discourse on leadership within the context of professional sports, shedding light on the intricacies of managing high-performance teams in the competitive world of football. By examining Jose Mourinho's leadership style, this paper not only offers valuable insights for football enthusiasts but also provides leadership scholars and practitioners with a compelling case study on effective leadership in dynamic and challenging environments